Agribisnis Ubi Kayu (Manihot Esculenta Crantz) di Kabupaten Cilacap - Eva Trisanti; Purwadi Purwadi; Ika Rosanah (Jurnal Dinamika Sosial Ekonomi, 2001)
This thesis is titled Cassava Agribusiness (Manihot Esculenta Crunte) In Kabupaten Cilacap. The study was carried out in Kecamatan Karangpucung, Kabupaten Cilacap and started from January 29 to April 29, 2001. To cope with the problem of food preservation, it is important to make food diservication program that is to be reled in aggregat ogribusiness system. Cassava is one of the ideal plants used in agribusiness system. This study aimed to find out the relationship between subsystems in cassava agribusiness in  Kabupaten Cilacap. It was also directed to find out the trend of cassava and-tapioca prices. The study employed basic descriptive analytical method. Sampling of kecamatan, desa, merchandiser and manufacturing industry used proposive sample method, while sampling of farmers used simple random sample method trend. Data collected were primary and secondary data taken by the interview record, and observation methods. Data analysis exerted tabulation and linier-trend analyses. The results of analyses indicated that cassava agribusiness activity is still isolated between writs of activity. The distribution of revenues and profits is not equal and the tendency of cassava production and price as well as the price of tapioca trend to increase. So cassava agribusiness system is necessary to be improved in the aggregateKeywords: agribusiness system, revenues and profits, production and price.